2017
DOI: 10.1007/7651_2017_47
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Super-hydrophobic Microbioreactor to Generate and Boost Pancreatic Mini-organoids

Abstract: Cell remarkable ability to self-organize and rearrange in functional organoids has been greatly boosted by the recent advances in 3-D culture technologies and materials. This approach can be presently applied to model human organ development and function "in a dish" and to predict drug response in a patient specific fashion.Here we describe a protocol that allows for the derivation of functional pancreatic mini-organoids from skin biopsies. Cells are suspended in a drop of medium and encapsulated with hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Encapsulation of cells in microbioreactor material with hydrophobic properties may further boost the formation of functional organoids that are not only protected by the supporting surface, but are also provided with optimal gas exchange between the interior liquid and the surrounding environment (Fig. 3; Arbatan et al 2012;Sarvi et al 2013Sarvi et al , 2015Tian et al 2013;Serrano et al 2015;Brevini et al 2017). Together, accumulating evidence indicates that, similar to soluble growth factors, cell morphology and the mechanical properties of the cellular microenvironment can affect both cell growth and cell differentiation.…”
Section: Mechanical Signals Control Cell Fatementioning
confidence: 99%
“…Encapsulation of cells in microbioreactor material with hydrophobic properties may further boost the formation of functional organoids that are not only protected by the supporting surface, but are also provided with optimal gas exchange between the interior liquid and the surrounding environment (Fig. 3; Arbatan et al 2012;Sarvi et al 2013Sarvi et al , 2015Tian et al 2013;Serrano et al 2015;Brevini et al 2017). Together, accumulating evidence indicates that, similar to soluble growth factors, cell morphology and the mechanical properties of the cellular microenvironment can affect both cell growth and cell differentiation.…”
Section: Mechanical Signals Control Cell Fatementioning
confidence: 99%
“…Thanks to all these unique properties, together with the easy manipulation and the high reproducibility and efficiency, liquid marbles have found numerous applications in the field of microfluidics, storage, transportation, and mechanical computation [ 73 , 74 , 75 , 76 ], as well as in the chemical and biological areas [ 77 ]. Recently, several studies have pointed to micro-bioreactors as ideal platforms, essential for biomedical applications and culture of microorganisms or cells of different types, spanning from oocyte [ 78 ], cardiac [ 79 ], pancreatic [ 80 ], toroid [ 81 ], and olfactory ensheathing [ 82 ] to high plasticity cells [ 32 ]. In particular, we demonstrated that cell encapsulation in micro-bioreactors induces distinctive 3D cell rearrangements and specific cell-to-cell interactions [ 32 ].…”
Section: D Cell Culture Systemsmentioning
confidence: 99%
“…Optical metabolic imaging is highly sensitive in revealing metabolic alterations 1–2 h following treatment with effective drugs, and such changes correlate with the expected response (i.e., HER2 expression in breast cancer) [ 105 ]. Further, optical metabolic imaging distinguishes cell types and drug response [ 18 , 29 , 41 , 62 , 63 , 106 , 107 ]. For instance, fibroblasts from PDAC organoids show drug response, despite no overt cell death enhancement [ 94 ].…”
Section: Applications Of Ptosmentioning
confidence: 99%